Experimental Study on Scour Model of Wujiagang Bridge Pier. Issue 1 (February 2021) - Li, Zhijing; Shan, Miner; Huang, Jiancheng; Zhou, Yinjun
Abstract: Local scouring of bridge piers is one of the main causes of structural damage and even water damage. In this study, an experimental study on scour model of Wujiagang bridge pier is carried out, the results show that the scope and depth of the pier scouring pit are closely related to the flow and water depth at the pier location, the maximum scouring depth and the scope of the scouring pit increase with the increase of unit-width discharge.